2021
DOI: 10.1101/2021.06.29.449897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced translation of leaderless mRNAs under oxidative stress in Escherichia coli

Abstract: The bacterial response to oxidative stress requires the adaptation of the proteome to the hostile environment. It has been reported that oxidative stress induces a strong and global inhibition of both, transcription and translation. Nevertheless, whereas it is well known that transcription of a small group of genes is induced thanks to transcription factors such as OxyR and SoxR, an equivalent mechanism has not been described for translation. Here we report that whereas canonical translation that depends on Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…In fact, our previous work has shown that addition of four codons is enough to report differences in the efficiency of translation of those codons ( Elgamal et al, 2014 ; Rojas et al, 2018 ; Leiva et al, 2020 ). Also, we have observed that under these conditions the stability of different segments of the reporter mRNA is similar ( Leiva et al, 2021 ). Therefore, we expect that changes in transcript level or alterations of translation initiation will affect the synthesis of GFP and mCherry in a similar manner.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…In fact, our previous work has shown that addition of four codons is enough to report differences in the efficiency of translation of those codons ( Elgamal et al, 2014 ; Rojas et al, 2018 ; Leiva et al, 2020 ). Also, we have observed that under these conditions the stability of different segments of the reporter mRNA is similar ( Leiva et al, 2021 ). Therefore, we expect that changes in transcript level or alterations of translation initiation will affect the synthesis of GFP and mCherry in a similar manner.…”
Section: Resultsmentioning
confidence: 87%
“…As mCherry translation initiated by the same mechanism in all reporters, we use it as an internal control for normalization. Although lmRNA translation of most genes is less efficient than SD translation under non-stress conditions, we have recently observed that under oxidative stress induced by 250 μM paraquat, lmRNA translation is activated ( Leiva et al, 2021 ). Using these new set of SD reporters, we observed that changes in the selection of Leu codons added to the vector led to a 6.4-fold difference in GFP synthesis under non-stress conditions ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations